A FRAMEWORK FOR QUANTITATIVE CYBER RESILIENCE ASSESSMENT OF NETWORK ARCHITECTURES IN EDUCATIONAL INSTITUTIONS - BAŠIĆ, Ana; VIDUKA, Dejan; JOVANOVIĆ, Dražen (Journal of process management and new technologies, 2026)
This paper investigates the development and application of an integrated framework for the quantitative assessment of cyber resilience of network architectures in educational institutions. Resilience assessment criteria were identified and mapped to the NIST Cybersecurity Framework to cover key functional areas of cybersecurity, while the ISO 31000 standard was applied to assess disruption scenarios, including cyber-attacks and network infrastructure failures. The PIPRECIA-S method enables precise weighting of criteria based on expert assessments, and the H-SCRM methodology allows quantitative evaluation of network alternatives according to defined criteria and scenarios. The results show that the hybrid cloud-managed network architecture achieves the highest level of cyber resilience, while software-defined networking and traditional LAN architecture achieve lower global resilience index values. Sensitivity analysis confirms the stability of the ranking of alternatives and the robustness of the proposed model. The paper provides practical guidelines for improving network security and decision-making in educational institutions through an integrated approach to risk and resilience management.
Keywords: Cyber resilience; educational institutions; NIST CSF; ISO 31000; PIPRECIA-S; H-SCRM